(untitled) (Research, Society and Development, 2025)
Creole cowpea varieties exhibit broad genetic variability and represent valuable resources for participatory breeding programs. This study aimed to analyze genetic parameters and estimate correlations among morpho-agronomic traits in creole cowpea genotypes grown for green grain production from the germplasm bank of IFPE – Vitória de Santo Antão. Ten genotypes obtained from the IFPE germplasm bank and rural communities in Itaquitinga and Goiana, Pernambuco, were evaluated. The experiment was conducted in a randomized block design with four replications, using plots composed of 2 m rows spaced 0.80 m between rows and 0.40 m between plants. Twenty quantitative traits were measured following descriptors adapted from Bioversity International. Data were subjected to analysis of variance, Scott–Knott test (p<0.05), Mahalanobis distance and genetic correlations. Significant differences were observed for 19 traits, forming up to seven groups. Genotype AC1 showed superior performance for green grain yield, indicating suitability for organic production systems. Hundred dry grain weight, number of seeds per pod and fresh grain weight of ten pods were the most promising traits for indirect selection. The results demonstrate genetic variability among the evaluated genotypes, supporting the selection of superior varieties.